The role of informatics in the development of the performance of the professor from the perspective of teaching at the University of Garmian - Mohammed, Haidar Salah (Journal of University of Human Development, 2016)
The research aims to identify the role of information technology in the development of university professor performance from the perspective of faculty members in Garmeyan / Kalar University, as well as to identify the degree of availability of information assets at the university, and the skill of information for teachers, and constraints. To achieve this, I rely The search sample of professors Garmeyan University (within the geographical location of the city of Kalar) consisting of (40) as a teacher, which formed 35% of the study population, has been collecting data using a questionnaire composed of four sections: Section I: included preliminary information and section II: This included paragraphs information on the university’s assets in the field of IT, and section III includes informatics areas, which included 29 items distributed among three sub-areas, namely (resource of knowledge, software, hardware and tools), section IV has included question about the main obstacles to the employment of informatics at the university. It was processing the data statistically using the arithmetic mean and standard deviation, the research found a number of conclusions the most important, the Informatics major role in the development of university professor performance from the viewpoint of the sample surveyed, as well as having some of the obstacles employ informatics in the field of university professor tasks.